Successful Management of Malignant Glaucoma with Pars Plana Vitrectomy and Glaucoma Drainage Device Implant - Rosalia Adriani Malika; Noviana K. Vivin; Dewi Rosarina (Vision Science and Eye Health Journal, 2023)
Introduction: Malignant glaucoma is a rare condition with challenging management. It is diagnosed by central and peripheral shallowing or flattening of the anterior chamber and increased intraocular pressure (IOP) without posterior segment abnormality (suprachoroidal effusion or hemorrhage of patent iridotomy). It can be managed by pars plana vitrectomy (PPV). Case Presentation: A 59-year-old man presented to the emergency unit in Undaan Eye Hospital, Surabaya complaining of pain and blurry vision in his left eye after being hit by a rope. Secondary glaucoma with posterior lens luxation was diagnosed in the left eye. The patient was given topical and oral glaucoma medications. Vitrectomy with endo laser and endo fragmentation was performed three months later with normal IOP. A retinal break was detected at five o’clock, and sulphur hexafluoride (SF6) was given during vitrectomy. Malignant glaucoma was diagnosed by flattening the anterior chamber after vitrectomy with left eye IOP of 31 mmHg. The left eye IOP remained elevated in the following months, and the pain persisted. However, topical and oral anti-glaucoma medications, topical cycloplegics, and steroids were already given. The cornea became hazy due to uncontrolled IOP. A left eye PPV with a glaucoma drainage devices (GDD) implant was conducted. Nevertheless, his left eye visual acuity did not improve (1/300). Besides, his left eye IOP was normal without topical and oral glaucoma medications. Conclusions: PPV offers reliable and prompt treatment for malignant glaucoma with a low complication rate. The patient’s vision can be preserved by lowering the IOP, preventing further optic nerve damage.